Field Test of a CO2 Cascade Air-source Heat Pump - Li Xiaoyu; Ma Li; Shi Lin; Xu Wei; Wang Tiansheng (Zhileng xuebao)
Carbon dioxide (CO2) air-source heat pumps have broad application prospects because of their excellent environmental protection potential and thermal performance. In this study, the CO2 cascade air-source heat pump was implemented in distributed central heating systems in a public building in Qinhuangdao City and a residential building in Shijiazhuang City. Both cases were tested and analyzed to explore the uncertainty of measurements and the operation performance in extremely cold conditions as per the Standard for Energy Efficiency Test of Public Buildings JGJ/T 177—2009 and the Standard for Energy Efficiency Test of Residential Buildings JGJ/T 132—2009. Based on the uncertainty analysis, the relative combined standard uncertainty ranges of COP (coefficient of performance) of #2 units operating at various ambient temperatures in Qinhuangdao and Shijiazhuang were found to be 4.27%–5.87% and 1.90%–4.36%, respectively. These ranges reveal that the measurements have high reliability. The measured daily heating COP of #1 and #2 units in Qinhuangdao are 2.75–3.09 and 2.76–3.15, respectively, when the outdoor daily temperature range is -10.9–2.5 °C. Even in the lowest outdoor temperature (-18 °C), the heating COP of #1 and #2 unitscan still reach 2.19 and 2.88, respectively. When #1 and #2 units operate in Shijiazhuang with the outdoor daily temperature being -6.6–12.5 °C, the measured daily heating COP are 2.32–3.38 and 2.21–3.06, respectively. The analysis of these two projects shows that the heating COP of the CO2 cascade air-source heat pump is not sensitive to the ambient temperature in extremely cold conditions.